HUBUNGAN BEBAN KERJA MENTAL DENGAN KEJADIAN HIPERTENSI PEMADAM KEBAKARAN DI DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KOTA TANGERANG SELATAN 2021 - Anissa Nur Alifia Asrial, (2021)
Hypertension is an abnormal medical condition which could occur to firefighters, usually caused by high fire accident rate. Data shows that on 2019 there were 114 fire accident and the data rises up to 130 fire accident on 2020. Heavy mental workload mainly caused by the need for firefighter to be mentally prepared for emergency responses at any time and condition. The purpose of this study was to analyze the correlation of mental workload and the people characteristic with the hypertension incidences among firefighters in Tangerang Selatan. This was a quantitative study under analytic observation and a cross-sectional design study. Sample used in this study measured with stratified random sampling resulted 103. Instrument used in this study are digital sphygmomanometer and NASA-TLX workload questionaire. This study starts on May until July 2021. The data was analyzed by using chi square test. The results of this study were 53.4% of workers suffers from hypertension and 56,3% workers experiences over workload. The analytical results of the statistic test showed variables with significant correlation with significance of age (P-value = 0.002), BMI (P-value = 0.02), and mental workload (P-value = 0.028). Therefore, workers were suggested to wearing Personal Protective Equipment (PPE) correctly, consuming more healthy food, and working out routinely.